Microfoundations of dynamic capabilities in artificial intelligence adoption for competitive advantage - Hasni Dyah Kurniawati (Indonesian Institute For Counseling, Education and Therapy, 2026)
This study explored the role of dynamic capabilities in enhancing corporate competitive advantage through the integration of artificial intelligence and managerial microfoundations. The research addressed the growing need for organizations to adapt to rapid technological changes and increasingly complex competitive environments. Using a qualitative literature review design, this study systematically analyzed 42 peer-reviewed sources retrieved from Scopus, Web of Science, ScienceDirect, SpringerLink, and Google Scholar. Sources were selected based on their relevance to dynamic capabilities, AI adoption, and microfoundational perspectives in strategic management. Data were analyzed using qualitative content analysis and thematic analysis. The findings revealed that the reviewed literature consistently indicates that dynamic capabilities, operationalized through sensing, seizing, and reconfiguring processes, are enhanced by the integration of AI technologies. However, the results also showed that the effectiveness of these capabilities depended heavily on managerial cognition, skills, and decision-making capacity. The study revealed that AI functioned not as a standalone driver of competitive advantage, but as an embedded component within organizational capabilities that required human interpretation and strategic alignment. Furthermore, variations in organizational outcomes highlighted the importance of micro-level factors in determining the success of technology adoption. The study concluded that the interplay between technological capabilities and human agency was essential for achieving sustainable competitive advantage. These findings contributed to a more comprehensive understanding of strategic management in the digital era and provided insights for both academic development and managerial practice.